2020
DOI: 10.2196/16979
|View full text |Cite
|
Sign up to set email alerts
|

Improving a Web-Based Tool to Support Older Adults to Stay Independent at Home: Qualitative Study

Abstract: Background Older adults desire to stay independent at home for as long as possible. We developed an interactive website to inform older adults and caregivers about ways to achieve this. Objective This study aimed to perform an in-depth exploration among potential end users about how to improve the interactive website to better inform older adults and caregivers about ways to stay independent at home. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Among the 28 included studies, 14 (50%) were quantitative [ 37 - 48 , 63 , 64 ], 7 (25%) were qualitative [ 49 - 55 ], and 7 (25%) used mixed methods [ 56 - 62 ]. Studies were most frequently conducted in the United States [ 38 , 41 , 45 - 48 , 50 , 53 , 58 , 60 ], the Netherlands [ 37 , 55 , 57 , 59 ], the United Kingdom [ 54 , 62 ], and Australia [ 52 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the 28 included studies, 14 (50%) were quantitative [ 37 - 48 , 63 , 64 ], 7 (25%) were qualitative [ 49 - 55 ], and 7 (25%) used mixed methods [ 56 - 62 ]. Studies were most frequently conducted in the United States [ 38 , 41 , 45 - 48 , 50 , 53 , 58 , 60 ], the Netherlands [ 37 , 55 , 57 , 59 ], the United Kingdom [ 54 , 62 ], and Australia [ 52 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Television was also found to be used to a somewhat lesser extent, but we included it in this paper due to ease-of-use and high accessibility across patient groups. Within the representative studies assessed in this study, apps/web-based technology had disease-specific targets, while the other technologies were primarily used in elderly patients, where the desire for individualized and tailored care is high [ 60 ]. Through analyzing the studies, we identified usability, scaling, and data management as important research areas regardless of eHealth implementation.…”
Section: Discussionmentioning
confidence: 99%
“…From March– April 2020 medical students from the University of Queensland Ochsner Clinical School (UQ-OCS) attempted to train MVC patients to perform telehealth visits with the Epic MyChart platform. MyChart is a self-service web portal offered by most Epic healthcare organizations that allows patients to access their medical records and perform telehealth and eHealth services [ 17 ]. UQ-OHS students spent on average 5 hours per patient performing one-on-one training and coaching over the phone on telehealth visit navigation.…”
Section: Methodsmentioning
confidence: 99%
“…These were all manually reviewed in full, and 85 articles were further excluded based on inclusion criteria, and the final 22 articles were included in the meta-synthetic review. After the exclusion of many tools based on our search and exclusion parameters the following 'toolkits' were selected because of their focus on multidomain literacies of interest: READHY, eHEALS, eHLF, eHLA, and eHLQ [12, [16][17][18][19]. We identified key components of each tool that addressed the telehealth navigation trouble points identified in our outreach, while being mindful of selecting components that would be practical for use with older adult and low literate populations.…”
mentioning
confidence: 99%